Characterization of the Cryptic AV3 Promoter of Ageratum Yellow Vein Virus in Prokaryotic and Eukaryotic Systems - Wang, Wei-Chen; Wu, Chia-Ying; Lai, Yi-Chin; Lin, Na-Sheng; Hsu, Yau-Heiu; Hu, Chung-Chi (PloS one, 2014)
A cryptic prokaryotic promoter, designated AV3 promoter, has been previously identified in certain begomovirus genus, including ageratum yellow vein virus isolate NT (AYVV-NT). In this study, we demonstrated that the core nucleotides in the putative -10 and -35 boxes are necessary but not sufficient for promoter activity in Escherichia coli, and showed that AYVV-NT AV3 promoter could specifically interact with single-stranded DNA-binding protein and sigma 70 of E. coli involved in transcription. Several AYVV-NT-encoded proteins were found to increase the activity of AV3 promoter. The transcription start sites downstream to AV3 promoter were mapped to nucleotide positions 803 or 805 in E. coli, and 856 in Nicotiana benthamiana. The eukaryotic activity of AV3 promoter and the translatability of a short downstream open reading frame were further confirmed by using a green fluorescent protein reporter construct in yeast (Saccharomyces cerevisiae) cells. These results suggested that AV3 promoter might be a remnant of evolution that retained cryptic activity at present.